EBV Lymphoproliferative Disease after Hematopoietic Stem Cell Transplant - Rouce, Rayne H (Curr Opin Hematol, 2014)
PURPOSE OF REVIEW: EBV reactivation can cause significant morbidity and mortality after allogeneic hematopoietic stem cell transplant (SCT). Delays in reconstitution of EBV-specific T lymphocyte activity can lead to life-threatening EBV lymphoproliferative disease (EBV-PTLD). This review highlights recent advances in the understanding of pathophysiology, risk factors, diagnosis, and management of EBV viremia and PTLD. RECENT FINDINGS: During the past decade, early detection strategies, such as serial measurement of EBV-DNA load, have helped to identify high-risk patients and to diagnose early lymphoproliferation. The most significant advances have come in the form of innovative treatment options, including manipulation of the balance between outgrowing EBV-infected B cells and the EBV cytotoxic T lymphocyte (EBV-CTL) response, and targeting infected B cells with monoclonal antibodies, chemotherapy, unmanipulated donor lymphocytes, and donor or more recently third party EBV-CTLs. Defining criteria for preemptive therapy and remains a challenge. SUMMARY: EBV reactivation is a significant complication after SCT. Continued improvements in risk-stratification and treatment options are required to improve the morbidity and mortality caused by EBV associated diseases. Current approaches use Rituximab to deplete B cells or adoptive transfer of EBV-CTL to reconstitute immunity. The availability of rapid EBV specific T cell products offers the possibility of improved outcomes.